The tension between business process modelling and flexibility: revealing multiple dimensions with a sociomaterial approach - Albuquerque, João Porto de; Christ, Marcel (The journal of strategic information systems, 2015)
Business process modelling has contradictory effects on flexibility: on the one hand, recent approaches to process modelling in organisations have been used to pursue flexibility as a strategic goal. On the other hand, the display of organisational practices in models and adherence to these models might reduce the degree of organisational flexibility. In order to shed new light on this paradox, this article adopts a sociomaterial analytical approach based on the Actor-Network Theory to develop a multidimensional understanding of flexibility as a relational effect of sociomaterial networks. A case study, carried out of a process modelling project within a large aircraft maintenance corporation, shows that the influence of process modelling on flexibility is not confined to the elements explicitly modelled in the diagrams (‘what’), but also span informal aspects of work practices (‘how’) and the extent of accountability in the organisation (‘who’). Therefore, the relative degree of flexibility that emerges from process modelling should be analysed along each dimension produced within the sociomaterial networks of the organisation.